2004
DOI: 10.1038/nature02649
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale phylogenetic architecture of a complex bacterial community

Abstract: Although molecular data have revealed the vast scope of microbial diversity, two fundamental questions remain unanswered even for well-defined natural microbial communities: how many bacterial types co-exist, and are such types naturally organized into phylogenetically discrete units of potential ecological significance? It has been argued that without such information, the environmental function, population biology and biogeography of microorganisms cannot be rigorously explored. Here we address these questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
389
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 464 publications
(424 citation statements)
references
References 28 publications
22
389
2
Order By: Relevance
“…Only a few studies have revealed the microdiversity of free-living bacterial populations (1,29,42,45). The investigated PnecC population differed from these populations in a low microdiversity and a strongly uneven population structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only a few studies have revealed the microdiversity of free-living bacterial populations (1,29,42,45). The investigated PnecC population differed from these populations in a low microdiversity and a strongly uneven population structure.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that a Polynucleobacter population with an extremely low intraspecific diversity and an uneven structure numerically dominated the bacterioplankton community in the investigated habitat. This low intraspecific diversity is in strong contrast to the high intraspecific diversities found in marine bacterial populations.Microdiversity of prokaryotes, i.e., the genetic diversity within species-like (Ͼ97% similarity of 16S rRNA genes) phylogenetic groups, receives increasing attention in microbial ecology (1,5,18,19,24,28); however, the ecological significance of this diversity is still unknown. The coexistence of different bacterial genotypes belonging to the same species-like phylogenetic group is well documented for marine (1,18,19,35,45) and freshwater habitats (8,9,10,11,27,30,43).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the 16S sequences of all the piezophiles share high similarity with those of nonpiezophilic isolates from Antarctica. Moreover, some genera containing piezophiles (Colwellia, Psychromonas, and Moritella) appear to be largely restricted to cold waters of various depths and are underrepresented in rRNA surveys (1) and absent from environmental shotgun sequences (53) obtained from temperate waters.…”
Section: Resultsmentioning
confidence: 99%